Political relations between Oman and Saudi Arabia (1971)
This file relates to relations between Oman and Saudi Arabia. It contains correspondence, press extracts and situation reports concerning: The visit of an Omani delegation to Saudi Arabia The rumours that an Imamate of Oman office has reopened in Dammam The possible visit of the Sultan of Oman Qaboos Bin Saeed Al Said to Saudi Arabia and Iran; his eventual decision to call off the visits and travel directly to London; and contacts between the Saudi administration and the Sultan HMG’s efforts to remove itself from acting as a ‘middle-man’ between Saudi Arabia and Oman A letter from the Saudi Minister of Petroleum and Mineral Resources Ahmad Zaki Yamani to Petroleum Development (Oman) Limited accusing it of drilling in Saudi territory; the damage this caused to Saudi-Omani relations; HMG’s efforts to establish whether this is an officially sanctioned Saudi approach Reports from Shell and Qatar of Saudi troop movements in Dhofar and Rub' Al Khali The impact of the Saudi disposition towards Oman on its postponement of Arab League membership The suggestion of a settlement between the Sultan and the Imam of Oman Ghalib Bin Ali Al Hina'i; the Sultan’s offer of the right to return to Oman to Ghalib, with the title of Mufti, provided he renounce the Imamate and swear loyalty; and efforts to establish Ghalib’s response to this offer Headquarters British Forces Gulf’s (HQBFG) reports on military operations in Dhofar US concern over the state of Oman-Saudi Arabia relations The improvement of relations between Oman and Saudi Arabia, including recognition of Oman by the latter, a successful visit to Saudi Arabia by the Sultan, and the issuing of a joint statement by the Sultan and the Ruler of Saudi Arabia King Faisal Bin Abdul Aziz Al Saud
Keywords: Relations – Oman – Arabie Saoudite

إمارات الساحل وعمان والدولة السعودية الاولى 1793-1818 - عبد الله, محمد مرسي (المكتب المصري الحديث, 1978)
Keywords: Relations – Oman – Arabie Saoudite

A Study of Suʿūdī relations with Eastern Arabia and ʿUmān - Rashīd, Zāmil Muḥammad ar- (McGill University, 1979)
Pendant la deuxieme moitie du dix-huitième siècle, la principauté Su'üdite de al-Dir'iyah devint un état puissant à la suite de ses campagnes militaires en faveur de la réforme religieuse et politique. Elle attira d'abord l'Arabie Centrale dans son orbite, pour ensuite annexer la région d'al-Hasa. Au début du dix-neuvième siècle, les Su'üdis entrent en relation avec l'Arabie Orientale et le 'Uman, où ils devaient jouer pendant de nombreuses années un rôle dominant dans la vie sociale, religieuse et politique. Ce memoire tente d'examiner le développement historique des relations Su'üdites avec l'Arabie Orientale et le 'Uman et relève les mobiles de l'expansion Su'ûdite ainsi que la nature et l'étendue de leur influence, qui dura jusqu'en 1871. A cette date, les Turcs occupèrent al-Hasa, éteignant le règne Su'ùdi et entraînant leur éventuelle disparition de l'Arabie Orientale et du 'Uman.
Keywords: Relations – Oman – Arabie Saoudite